Designing an efficient bifunctional electrocatalyst heterostructure. Issue 74 (25th August 2021) - Sachdeva, Parrydeep Kaur; Gupta, Shuchi; Bera, Chandan
Abstract : Doped graphene and Janus molybdenum dichalcogenide heterostructures form efficient bifunctional electrocatalysts for oxygen and hydrogen evolutions with boosted electron transport at the heterojunction. Abstract : Oxygen and hydrogen evolutions are the two fundamental processes involved in electrocatalytic water splitting. Two dimensional (2D) transition metal dichalcogenides (TMDCs) and graphene-based materials are regarded as the emergent catalysts for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Herein, doped graphene and molybdenum dichalcogenide heterostructures are evaluated for their catalytic activity using density functional theory (DFT). The Janus MoSSe and P-doped graphene heterostructure is found to have the best electrocatalytic activities with smaller overpotential values ( η OER = 1.67 V and η HER = 0.10 V) as compared to those of the parent monolayers graphene ( η OER = 1.85 V and η HER = 1.80 V) and MoS2 ( η OER = 2.99 V and η HER = 1.72 V).